Conversations Surrounding the Use of DNA Tests in the Family Reunification of Migrants Separated at the United States-Mexico Border in 2018 - Wagner, Jennifer K.; Madden, Diana; Oray, Valedie; Katsanis, Sara H. (Frontiers in Genetics, 2019)
In April 2018, the U.S. implemented a “zero-tolerance” immigration policy that would lead to the separation of more than 2,000 migrant families over the following months. By early summer 2018, the policy and resultant family separations had generated a media storm that swept up the public. In early June, the government announced its consideration of DNA testing to aid in the detection of human trafficking in immigration contexts. By mid-June, as the government retracted the child separation policy, the public began questioning how children and adults would be reunited and discussing the potential usefulness of DNA testing for those reunifications. In early July, the government announced that DNA testing was indeed being used, and by mid-July the public’s outrage over the use of DNA was strong. We set out to examine the public dialogue on DNA testing¬–including misunderstandings and miscommunications–both in newspaper coverage and on Twitter in the two-month summer period of 2018, at the height of public discussion of migrant family separations and then reunifications. We performed database searches identifying 263 newspaper articles and used Twitter’s advanced search function identifying 153 Tweets containing discussion of the use of DNA for migrant family reunification. Upon the resulting sources, we performed content analysis, analyzing for slant on the immigration policy and the use of DNA tests using a combination of open and closed codes. Our analysis showed that perspectives on the use of DNA diverged in connection with perspectives on the immigration policy, and that there was a contrast among the cohorts in the stated utility of DNA testing. These findings offer insight into (a) how DNA testing in a highly politicized immigration context was represented in media coverage and (b) the public’s understanding of the role that DNA testing could or should play in immigration. By detailing the role that comments from experts, stakeholders, and the public played in these discussions, we hope to provide lessons for communications with the public about future non-medical applications of genetic technologies.